Alternative Environmental Dispute Resolution Based On Local Wisdom Of Banjar Traditional Community - Rahmawati, Diana; Tavinayati, Tavinayati (Scholar Center, 2025)
The purpose of this study is first to identify the difficulties of the community as victims in resolving environmental disputes through the courts (litigation) and then to find a pattern of environmental dispute resolution outside the courts that can be applied in accordance with the values ??and local wisdom of the Banjar community. The research method used is normative legal research, namely examining the applicable legal norms related to the resolution of environmental disputes. The results of this study: First, in the Settlement of Environmental Disputes in court (litigation) there are several weaknesses, namely the formality of the court system, proof of the elements contained in Article 1365 BW, the burden of proof is on the plaintiff / victim. In addition, settlement through the Court requires a lot of court costs, a long time, and court decisions are not satisfactory because the settlement is win-lose, less responsive, and no special court for environmental cases has been formed. Nevertheless, Law No. 32/2009 and and Government Regulation Number 54 of 2000 has opened up opportunities for the establishment of an Environmental Dispute Resolution Service Provider Institution outside the courts in the regions. In order to be more effective, a pattern of dispute resolution can be developed which has become a culture or customary law in the Banjar community, namely the